Family Structures and Family Values in the Theory of Income Distribution - Ishikawa, Tsuneo (Journal of Political Economy, 1975)
This paper analyzes household decisions concerning education and bequest. Specifically, an integrated model of life-cycle savings and investment in human capital is used to investigate the effects of two institutional dimensions: (1) family generational structures and (2) family values placed on intergenerational welfare. The analysis shows that these two dimensions are, in fact, important determinants of the size distribution of income both in the short run and in the long run.